Neuronally-derived tau is increased in experienced breachers and is associated with neurobehavioral symptoms - Katie A. Edwards (Nature Portfolio, 2021)
Abstract Military and law enforcement breachers are exposed to many low-level blasts during their training and occupational experiences in which they detonate explosives to force entry into secured structures. There is a concern that exposure to these repetitive blast events in career breachers could result in cumulative neurological effects. This study aimed to determine concentrations of neurofilament light (NF-L), tau, and amyloid-beta 42 (Aβ42) in serum and in neuronal-derived extracellular vesicles (EVs) in an experienced breacher population, and to examine biomarker associations with neurobehavioral symptoms. Thirty-four participants enrolled in the study: 20 experienced breachers and 14 matched military or civilian law enforcement controls. EV tau concentrations were significantly elevated in experienced breachers (0.3301 ± 0.5225) compared to controls (−0.4279 ± 0.7557; F = 10.43, p = 0.003). No statistically significant changes were observed in EV levels of NF-L or Aβ42 or in serum levels of NF-L, tau, or Aβ42 (p’s > 0.05). Elevated EV tau concentrations correlated with increased Neurobehavioral Symptom Inventory (NSI) score in experienced breachers (r = 0.596, p = 0.015) and predicted higher NSI score (F(1,14) = 7.702, p = 0.015, R 2  = 0.355). These findings show that neuronal-derived EV concentrations of tau are significantly elevated and associated with neurobehavioral symptoms in this sample of experienced breachers who have a history of many low-level blast exposures.